CD4+ CD25+ GARP+ regulatory T cells display a compromised suppressive function in patients with dilated cardiomyopathy. Issue 3 (29th March 2017) - Wei, Yuzhen; Yu, Kunwu; Wei, Hui; Su, Xin; Zhu, Ruirui; Shi, Huairui; Sun, Haitao; Luo, Quan; Xu, Wenbin; Xiao, Junhui; Zhong, Yucheng; Zeng, Qiutang
Summary: Dilated cardiomyopathy (DCM) is a lethal inflammatory heart disease and closely connected with dysfunction of the immune system. Glycoprotein A repetitions predominant (GARP) expressed on activated CD4 + T cells with suppressive activity has been established. This study aimed to investigate the frequency and function of circulating CD4 +   CD25 +  GARP + regulatory T (Treg) cells in DCM. Forty‐five DCM patients and 46 controls were enrolled in this study. There was a significant increase in peripheral T helper type 1 (Th1) and Th17 number and their related cytokines [interferon‐ γ (IFN‐ γ ), interleukin (IL‐17)], and an obvious decrease in Treg number, transforming growth factor‐ β 1 (TGF‐ β 1 ) levels and the expression of forkhead box P3 (FOXP3) and GARP in patients with DCM compared with controls. In addition, the suppressive function of CD4 +  CD25 +  GARP + Treg cells was impaired in DCM patients upon T‐cell receptor stimulation detected using CFSE dye. Lower level of TGF‐ β 1 and higher levels of IFN‐ γ and IL‐17 detected using ELISA were found in supernatants of the cultured CD4 +  CD25 +  GARP + Treg cells in DCM patients compared with controls. Together, our results indicate that CD4 +  CD25 +  GARP + Treg cells are defective in DCM patients and GARP seems to be a better molecular definition of the regulatory phenotype. Therefore, it might be an attractive stategy to pay more attention to GARP in DCM patients. Abstract : Dilated cardiomyopathy (DCM) is a lethal inflammatory heart disease and closely connected with dysfunction of the immune system. Our study indicates that the frequencies of CD4 +  CD25 +  GARP + regulatory T cells in patients with DCM are reduced and their suppressive function on responder T‐cell proliferation is compromised.